Perseverance and Recognition: The Struggle of JAGI Church in Establishing its Unitarian Christian Identity - Maola, Mochammad (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2024)
This article aims to examine the development, challenges, and dynamics of the JAGI Church concerning religious freedom in Indonesia. This research seeks to answer fundamental questions about the identity of the JAGI Church, its mission, its influence in Indonesia's social and religious realms, and the various challenges it faces in the form of discrimination. The research methodology applied to the JAGI Church study uses a qualitative descriptive approach. This research methodology also integrates a historical contextualization approach, which aims to provide a different understanding by placing these events in Indonesia's broader historical, social, and religious context. The results of this research demonstrate a deep understanding of the dynamics of religious freedom and the challenges faced by the JAGI Church in achieving official recognition, as well as describing their efforts in fighting for interreligious dialogue and creating an environment of mutual respect and tolerance. This article also links the JAGI Church case study with the thinking of religious freedom experts, thus providing new insight into the complexities of protecting and promoting religious freedom in the context of a multicultural society like Indonesia.